USING DICTOGLOSS TECHNIQUE TO INCREASE THE LISTENING COMPREHENSION ABILITY ON NARRATIVE TEXTS OF THE SECOND YEAR STUDENTS OF MTs MUAWWANAH SUNGAI PAGAR KAMPAR REGENCY - Rifki Afdhal Afdhal; Atni Prawati Prawati; Jismulatif ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: Listening is a basic skill that is very important to master and to support other skills such as speaking, reading and writing The aim of this research was to find out whether or not teaching listening by using dictogloss technique can increase the ability of the second year students of MTs Muawwanah Sungai Pagar in listening comprehension of narrative texts and to find out the factors caused the improvement on students’ listening comprehension ability. The participants of this research were 26 students of the second year students of MTs Muawwanah Sungai Pagar. This researchwas a classroom action research within two cycles. The data collection techniques were (1) observation sheet which was applied to know the students’ activities during teaching and learning process , (2) test was done to measure students’ achievement , and (3) field note was done to obtain imformation about teacher, the students’ activities and performance during the implementation of dictogloss technique. The research findings can be briefly explained as follows; firstly, the students’ ability in listening comprehension on narrative texts could be improved by using dictogloss technique. Before the research was done, the average score of students’ pre-test was 62.1. After the research has done for 2 cycles, the average score of students’ listening comprehension ability was 75.96. Secondly, the students’ activeness increased from cycle 1 to cycle 2. Keyword: Dictogloss Technique, Listening Comprehension, Narrative Texts